THE BASIC FEATURES OF TYPICAL BUYERS OF ORGANIC FOOD: Frequency of organic food purchases - Mitić, Vladimir (Journal of Agricultural Sciences (Belgrade), 2022)
The main aim of this research is to determine the frequency of organic food purchases in general and the basic demographic characteristics of typical buyers of organic food. Sample consist of 571 respondents of different sex, age, educational level, area of living, material and marital status. The research was conducted online using a Google questionnaire compiled for the purposes of this and related research, whose reliability has been adequate in previous research. The SPSS program was used for data processing. Due to the asymmetric distribution of scores on the measured variables, nonparametric techniques were aplayed. In addition to descriptive statistics, the Man Witney U test and the Kruskal – Wallis one-way analysis of variance were used to determine the statistical significance of the obtained differences in scores between groups of subjects. The obtained results showed that the frequency of purchasing organic food in Serbia is still low. Typical buyers of organic food are mostly women, older, have higher education and income. They usually live in an urban areas, in big cities, while their marital status seems to has no influence on their decision to purchaise an organic food and prod